Interdisciplinary Orthodontic and Surgical Management of Class III Malocclusion in Adult Patients - Camelia Szuhanek; Stefania Dumitrescu; Eduard Paraschivescu; Riham Nagib (Journal of Dentistry And Oral Implants, 2019)
The treatment of class III malocclusion differs depending on the age of the patient. In adult patients, alternatives include either orthodontic dentoalveolar compensation treatment or a combined ortho-surgical approach. The aim of this paper is to present the orthodontic and surgical treatment of a 24 year old adult patient with increased anterior face height, a class III skeletal pattern and mandibular asymetry. Previous orthodontic treatment with removable appliances obtained a 1 mm overbite and overjet. Intraorally, class III molar relationship was observed, proclined upper incisors, retroclined lower incisors and a deviated lower midline. The main complaint was facial esthetics which required surgical intevention. After pre-surgical orthodontic preparation the maxilla was repositioned by a Le Fort I osteotomy and the mandible was set back using the Obwegeser-Dal Pont method. Final assesment revealed both functional and esthetic dentofacial results. A combination of orthodontic treatment and orthognathic surgery is often required in adult patients with dental malocclusion and skeletal discrepancies.
Keywords: sagital skeletal discrepancies